Exploiting functional domains of GRK2/3 to alter the competitive balance of pro‐ and anticontractile signaling in airway smooth muscle. Issue 2 (16th October 2013) - Deshpande, Deepak A.; Yan, Huandong; Kong, Kok‐Choi; Tiegs, Brian C.; Morgan, Sarah J.; Pera, Tonio; Panettieri, Reynold A.; Eckhart, Andrea D.; Penn, Raymond B.
Abstract : To clarify the potential utility of targeting GRK2/3‐mediated desensitization as a means of manipulating airway smooth muscle (ASM) contractile state, we assessed the specificity of GRK2/3 regulation of procontractile and relaxant G‐protein‐coupled receptors in ASM. Functional domains of GRK2/3 were stably expressed, or siRNA‐mediated GRK2/3 knockdown was performed, in human ASM cultures, and agonist‐induced signaling was assessed. Regulation of contraction of murine tracheal rings expressing GRK2 C terminus was also assessed. GRK2/3 knockdown or expression of the GRK2 C terminus caused a significant (~30–90%) increase in maximal β‐agonist and histamine [phosphoinositide (PI) hydrolysis] signaling, without affecting the calculated EC50 . GRK2 C‐terminal expression did not affect signaling by methacholine, thrombin, or LTD4. Expression of the GRK2 N terminus or kinase‐dead holo‐GRK2 diminished (~30–70%) both PI hydrolysis and Ca 2+ mobilization by every Gq ‐coupled receptor examined. Under conditions of GRK2 C‐terminal expression, β‐agonist inhibition of methacholine‐stimulated PI hydrolysis was greater. Finally, transgenic expression of the GRK2 C terminus in murine ASM enabled ~30–50% greater β‐agonist‐mediated relaxation of methacholine‐induced contraction. Collectively these data demonstrate the relative selectivity of GRKs for the β2 AR in ASM and the ability to exploit GRK2/3 functional domains to render ASM hyporesponsive to contractile agents while increasing responsiveness to bronchodilating β‐agonist.—Deshpande, D. A., Yan, H., Kong, K.‐C., Tiegs, B. C., Morgan, S. J., Pera, T., Panettieri, R. A., Eckhart, A. D., Penn, R. B. Exploiting functional domains of GRK2/3 to alter the competitive balance of pro‐ and anticontractile signaling in airway smooth muscle. FASEB J. 28, 956–965 (2014). www.fasebj.org